ESTUDO PRELIMINAR DE VALIDAÇÃO CLÍNICA DO DIAGNÓSTICO DE ENFERMAGEM MOBILIDADE FÍSICA PREJUDICADA EM IDOSOS INSTITUCIONALIZADOS - Ângela Alessandri M. C. Almeida; Rosimere Ferreira Santana; Lorena Aparecida de Oliveira Araújo; Maria Márcia Bachion (Universidade Federal de Goias, 2001)
The Nursing Dianosis in the Taxonomy I of the North American Nursing Diagnosis Association need refinement. We have the objective to realize clinical validation of the Impaired Physical Mobility in elderly people who are in home institutions. Following a protocol, 2 experts realized simultaneously the clinical evaluation from 10 elderly people resident in home institution. We found majors defining characteristics (reduction of the moviment ability, diminuition of motion spaciousness, diminished flexbility, between others) and minors defining characteristics (diminution ability for use the sanitary, muscle weakness, between others ). This research contributes for the refinement of this diagnosis and its identification more safe with elderly people, what can help for precodes interventions.